Pathology of T-cell-mediated drug hypersensitivity reactions and impact of tolerance mechanisms on patient susceptibility. Issue 4 (2nd August 2022) - Line, James; Thomson, Paul; Naisbitt, Dean J.
Abstract : Purpose of review: T-cell-mediated drug hypersensitivity is responsible for significant morbidity and mortality, and represents a substantial clinical concern. The purpose of this article is to focus on T-cell reactions and discuss recent advances in disease pathogenesis by exploring the impact of tolerance mechanisms in determining susceptibility in genetically predisposed patients. Recent findings: Certain drugs preferentially activate pathogenic T cells that have defined pathways of effector function. Thus, a critical question is what extenuating factors influence the direction of immune activation. A large effort has been given towards identifying phenotypic (e.g., infection) or genotypic (e.g., human leukocyte antigen) associations which predispose individuals to drug hypersensitivity. However, many individuals expressing known risk factors safely tolerate drug administration. Thus, mechanistic insight is needed to determine what confers this tolerance. Herein, we discuss recent clinical/mechanistic findings which indicate that the direction in which the immune system is driven relies upon a complex interplay between co-stimulatory/co-regulatory pathways which themselves depend upon environmental inputs from the innate immune system. Summary: It is becoming increasingly apparent that tolerance mechanisms impact on susceptibility to drug hypersensitivity. As the field moves forward it will be interesting to discover whether active tolerance is the primary response to drug exposure, with genetic factors such as HLA acting as a sliding scale, influencing the degree of regulation required to prevent clinical reactions in patients.